A COMPARATIVE SYSTEMATIC REVIEW OF SPATIAL DISTRIBUTION OF HEAVY METAL CONTAMINATION IN AGRICULTURAL AND INDUSTRIAL SOILS - Salma, Ghina Yusriyyah; Pratama, Mochamad Adhiraga (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2026)
Soil-bound heavy metals have been a major and growing environmental issue in recent decades of time, especially across developing nations in the context of rapid urbanization and industrial development. So far, very few studies have examined the spatial distribution of heavy metal contamination in agri-and/or industrial soils. The objective of this review article is to analyze, identify, evaluate and synthesize the existing knowledge on heavy metal contamination in soils across diverse industrial and agri-based land uses worldwide. The PRISMA 2020 method was used in this review article, involving the selection of 22 journal articles that met the criteria for further study and discussion. Heavy metal contamination in soils is due mainly to industrial activities (82% of the studies) and agricultural activities (64%), whereas both sources of contamination were identified in 45% of the studies. On the other hand, the well-known spatial analysis methods for the spatial distribution of soil heavy metals are kriging and IDW. For the industrial sector, individual heavy metals such as Pb, Cr, Ni, and Zn are of greater concern than in the agricultural sector. These metals accumulate in the environment and the food chain, causing short-term and long-term diseases. The choice of spatial analysis techniques to examine the distribution of heavy metals can be modified based on the availability and reliability of the data. The results provide great guidance to researchers and policymakers in designing and implementing effective strategies for prevention, surveillance, and reduction of exposure to heavy metals worldwide.